种灌浆廊道永久伸缩缝渗水处理方法 (2018)
种灌浆廊道永久伸缩缝渗水处理方法，对裂缝表面进行打磨，去除缝面的杂物，并冲洗干净；将廊道伸缩缝上、下游及拱顶混凝土面整体凿槽，对伸缩缝周边的蜂窝、孔洞开凿至混凝土密实部位；利用电锤沿伸缩缝骑缝打孔；用堵漏胶沿缝中心埋设灌浆半管，灌浆半管的开口对准伸缩缝的中心线，灌浆半管管面开孔，引注浆管、排气管；沿灌浆半管管面安装膨胀止水条，封堵伸缩缝在堵漏过程中少量渗水；在堵漏胶表面刷底胶，填充塑性嵌缝止水材料；在塑性嵌缝止水材料表面，布设层橡胶止水带；利用环氧砂浆保护层，将开凿部位回填至廊道混凝土表面，并将廊道伸缩缝表面进行找平，收光。本发明可以大幅度提高大坝安全度，充分发挥水工建筑物的综合功能。 The invention relates to a water seepage treatment method for a permanent expansion joint of a grouting gallery. The surface of the cracking joint is polished, sundries on the joint face are removed, and the joint face is washed to be clean; the upstream and the downstream of the expansion joint of the gallery and an arch top concrete face are wholly subject to gouging, and honeycombs and holes in the periphery of the expansion joint are excavated to a concrete compaction portion; an electric hammer is used for punching holes along a perforation of the expansion joint; leaking stoppage glue is used for embedding a grouting semi pipe along the center of the joint, an opening of the grouting semi pipe is aligned with th